Enhanced Adaptability to Limited Water Supply Regulated by Diethyl Aminoethyl Hexanoate (DA-6) Associated With Lipidomic Reprogramming in Two White Clover Genotypes - Hassan, Muhammad Jawad; Qi, Hongyin; Cheng, Bizhen; Hussain, Shafiq; Peng, Yan; Liu, Wei; Feng, Guangyan; Zhao, Junming; Li, Zhou (Frontiers in Plant Science, 2022)
Membrane lipids reprogramming is one of the most important adaptive strategies in plant species under unfavorable environmental circumstances. Therefore, the present experiment was conducted to elucidate the effect of diethyl aminoethyl hexanoate (DA-6), a novel synthetic plant growth regulator, on oxidative damage, photosynthetic performance, changes in lipidomic profiles, and unsaturation index of lipids in two white clover (Trifolium repens) cultivars (Ladino & Riverdel) under PEG-6000-induced drought stress. Results revealed that drought stress significantly enhanced oxidative damage and decreased photosynthetic functions in both cultivars, however the damage was less in Riverdel. In addition, drought stress significantly decreased the relative content of monogalactocyl-diacylglycerol (MGDG), sulfoquinovosyl-diacylglycerol (SQDG), phosphatidic acid (PA), phosphatidyl-ethanolamine (PE), phosphatidyl-glycerol (PG), phosphatidyl-serine (PS), ceramide (Cer), hexosylmonoceramide (Hex1Cer), sphingomyelin (SM), and sphingosine (Sph) in both cultivars, while more pronounced decline was observed in Ladino. Exogenous application of DA-6 significantly increased the relative content of digalactocyl-diacylglycerol (DGDG), monogalactocyl-diacylglycerol (MGDG), sulfoquinovosyl-diacylglycerol (SQDG), phosphatidic acid (PA), phosphatidyl-ethanolamine (PE), phosphatidyl-glycerol (PG), phosphatidyl-inositol (PI), phosphatidyl-serine (PS), ceramide (Cer), hexosylmonoceramide (Hex1Cer), neutral glycosphingolipids (CerG2GNAc1), and sphingosine (Sph) in two cultivars under drought stress. DA-6-treated Riverdel exhibited significantly higher DGDG:MGDG ratio and relative content of sphingomyelin (SM) than untreated plants in response to water deficiency. Furthermore, the DA-6-pretreated plants increased unsaturation index of phosphatidic acid (PA) or phosphatidylinositol (PI) in ladino, ceramide (Cer) or hexosylmonoceramide (Hex1Cer) in Riverdel, and sulfoquinovosyl-diacylglycerol (SQDG) in both cultivars under water stress. These results suggested that DA-6 regulated drought tolerance in white clover could be associated with increased lipids content and reprogramming, higher DGDG:MGDG ratio, and improved unsaturation index of lipids contributing to enhanced membrane stability, integrity, fluidity, and downstream signaling transduction.